Insect Borers Killing Fire-scorched Chir Pine Trees and Their Control in Nahan Forest Division, Himachal Pradesh - Thapa, R. S.; Singh, Pratap (Indian Forester, 1990)
In Jamta Range in Nahan Forest Division, Himachal Pradesh a wide-spread fire broke nut in April-May, 1984 and number of chir pine trees slowly started dying one after the other even after 10 months of outbreak of fire. These trees Were being trapped for resin for many years by lip-and-cup method making deep and wide blazes leaving only narrow bark strips between two adjacent blazes. The study showed that the scorched bark-strips around the blazed area attracted two flat-headed borers, one the bark borer, Melanophilo ignicola and another the sap wood borer, Sphenoptera aterrima which badly damaged the bark and formed a girdle around the tree trunks resulting in slow death or trees Treatment with 1% lindane water emulsion around the tapped area was found very effective in protecting the trees from borers’ attack and there by preventing their mortality.